Basic quality control in routine MRI. (September 2016) - Maris, Thomas G.
Abstract : Aim: Magnetic Resonance Imaging (MRI) has evolved a valid clinical tool in everyday practice. Its unique capabilities of imaging soft tissue human anatomy and physiology with excellent spatial, temporal and contrast resolution explain its outstanding role in clinical imaging. The aim of this lecture is to present the rationale of Quality Control (QC) and Quality Assurance (QA) in MRI and to briefly present a set of basic QC tests that can ensure MRI system's performance and help on maintain diagnostic quality in routine clinical MRI examinations. Learning objectives: Understand the general rationale of QC and QA in MRI. Presentation of the AAPM 100 protocol. Basic procedures and methodologies. Presentation of accredited phantoms and tools used for basic QC and QA in MRI. Presentation of a set of basic QC tests for assessing MRI system's performance based solely on simple imaging post-processing methods. This will include assessments of the following system's parameters: – H0 static field homogeneity – Signal to Noise (SNR) and Contrast to Noise (CNR) measurements – Spatial Uniformity of SNR – Chosting Ratio and MR image uniformity – Geometric Distortion and Spatial Linearity – Slice thickness – High Contrast Spatial Resolution – Low Contrast Object Detectability